Bargaining and Worker Representation under New Zealand's Employment Contracts Legislation : A Review After Two Years - Harbridge, Raymond; Hince, Kevin (Relations industrielles / Industrial Relations, 1994)
This paper examines the significant shift in the central philosophic and léegislative base of labour relations in New Zealand since the adoption of the Labour Relations Act in 1987 and the Employment Contracts Act in 1991. It reports two empirical studies. The first examines the collective bargaining System. The second study reports the structure and membership of trade unions in New Zealand in this new environment.